EMPOWERING THE KARANG TARUNA YOUTH ORGANIZATION OF KARANG HARUM VILLAGE THROUGH TRAINING IN CHARCOAL BRIQUETTE PRODUCTION AND THE IMPLEMENTATION OF AUTOMATIC BRIQUETTE MOLDING TECHNOLOGY BASED ON RICE HUSK WASTE - Arnisa Stefanie; Dicki Dian Purnama; Bahar Amal; Zahra Kirani Nur Rahmah; Arsa Anedtha Itsna Putri (Jurnal Pengabdian Masyarakat Sabangka, 2026)
Karang Harum Village, Bekasi Regency, has an abundant potential of rice husk waste; however, its utilization is still limited to low-value burnt husk. Limited technology, low production skills, and the absence of a structured business unit prevent the community—particularly the youth organization—from optimizing the economic value of agricultural waste. This community service program aims to enhance the community’s capacity through briquette production training, the implementation of an automatic electric briquette molding machine, and business management assistance. The activities consist of socialization, technical training, managerial training, technology installation, and a four-month mentoring period. The results indicate a 61.3% improvement in participants’ knowledge, an increase in production capacity from 0 kg to approximately 100 kg per week, and the establishment of a youth-based independent business unit. The implemented technology successfully reduced production time by up to 60% and produced briquettes with more consistent quality standards. This program contributes to income generation, agricultural waste utilization, and the development of village-based renewable energy businesses.